Colony Collapse Disorder (CCD) in Honey Bees - Jamie Ellis (EDIS)
Revised! ENY-150, a 5-page illustrated fact sheet by Jamie Ellis, explains what is known about this problem threatening the beekeeping industry in the U.S. — its symptoms, theories about its cause, how it affects the general public, what’s being done, and management recommendations for beekeepers. Includes selected references. Published by the UF Department of Entomology and Nematology, July 2010.